ANALYSIS OF RISK FACTORS FOR THE OCCURRENCE OF NATURAL DISASTERS: ANALYSIS OF RISK FACTORS FOR THE OCCURRENCE OF NATURAL DISASTERS - Dimanova, Donika (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Management of crises caused by natural disasters is one of the main functions of the state. The ability of our country to respond adequately to constantly accompanying natural disasters is one of the main approaches to ensure security. Essential for the management of natural disasters are properly identified and defined risk factors and threats. Increasing the different by their nature emergencies throughout the country puts more strongly the questions about the effectiveness of forecasting and planning at national, institutional, regional and object level.